2023
DOI: 10.12968/jowc.2023.32.sup4b.s1
|View full text |Cite
|
Sign up to set email alerts
|

Best practice for wound repair and regeneration use of cellular, acellular and matrix-like products (CAMPs)

Abstract: There are currently over 80 biomaterials derived from autologous, allogeneic, synthetic and xenogeneic sources, or a combination of any or all these types of materials, available for soft-tissue coverage to effect wound closure. Often generically referred to as cellular and/or tissue-based products (CTPs), they are manufactured under various trade names and marketed for a variety of indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…The USP <51> standard provides a well-accepted test method for evaluating the effectiveness of a material against a broad spectrum of microorganisms [18]. The seven microorganisms selected in this study were chosen because of their known pathogenicity, representing a comprehensive range of microbes typically found in the wound environment [1,[6][7][8][11][12]20]. Gjødsbøl et al (2006) conducted a retrospective clinical study on 46 patients with chronic leg ulcers [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The USP <51> standard provides a well-accepted test method for evaluating the effectiveness of a material against a broad spectrum of microorganisms [18]. The seven microorganisms selected in this study were chosen because of their known pathogenicity, representing a comprehensive range of microbes typically found in the wound environment [1,[6][7][8][11][12]20]. Gjødsbøl et al (2006) conducted a retrospective clinical study on 46 patients with chronic leg ulcers [6].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced matrices have been utilized in wound repair for decades [12]. These products may be cellular or acellular in nature and can be derived from either autologous, allogeneic, xenogeneic, or synthetic sources [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per a consensus document recently developed, CAMPs are defined as "a broad category of biomaterials, synthetic materials or biosynthetic matrices that support repair or regeneration of injured tissues through various mechanisms of action". 11 A recent report by the Agency for Healthcare Research and Quality (AHRQ) found that there are more than 70 approved skin substitutes in the management of DFUs. 12 Skin substitutes have recently been evaluated in four different systematic reviews and meta-analyses [13][14][15][16] and have been shown to be effective with favourable healing rates and reduced time to healing within [12][13][14][15][16] weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced wound care products such as skin substitutes otherwise known as cellular, acellular, and matrix‑like products (CAMPs) can be used adjunctively with standard care in the management of DFUs. As per a consensus document recently developed, CAMPs are defined as “a broad category of biomaterials, synthetic materials or biosynthetic matrices that support repair or regeneration of injured tissues through various mechanisms of action” 11 . A recent report by the Agency for Healthcare Research and Quality (AHRQ) found that there are more than 70 approved skin substitutes in the management of DFUs 12 .…”
Section: Introductionmentioning
confidence: 99%